2017
DOI: 10.12693/aphyspola.132.879
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Mechanical Properties of Unidirectional and Woven Carbon, Glass and Aramid Fiber Reinforced Epoxy Composites

Abstract: In this study, mechanical behavior of epoxy composite reinforced by unidirectional and woven fiber is investigated experimentally. In the preparation of composite samples woven shaped glass, aramid and carbon fibers and unidirectional shaped glass and carbon fibers were used. Tension, compression and shear tests were carried out to determine mechanical properties of composites. It is seen from the test results, that unidirectional carbon fiber shows better performance than the glass fiber. Mechanical propertie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(49 citation statements)
references
References 20 publications
2
46
0
1
Order By: Relevance
“…During the bending of continuous fiber reinforced composites, the composite is compressed and tensioned. Polymer composites, in particular aramid fiber composites, are characterized by the weak transverse properties [ 44 , 45 ] and significantly lower compression compared to tension strength [ 46 ]. As a result, the bending strength depends primarily on the compressive strength, as the damage usually starts on the compressive side [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…During the bending of continuous fiber reinforced composites, the composite is compressed and tensioned. Polymer composites, in particular aramid fiber composites, are characterized by the weak transverse properties [ 44 , 45 ] and significantly lower compression compared to tension strength [ 46 ]. As a result, the bending strength depends primarily on the compressive strength, as the damage usually starts on the compressive side [ 30 ].…”
Section: Resultsmentioning
confidence: 99%
“…(1) Impregnation of textiles with epoxy resin (2) Autoclave curing at 60°C/12 h [40] Autoclave (1) Autoclave curing at 177°C/120 min/0.70 MPa or 121°C/90 min depending on the epoxy type [41] Hand lay-up (1) Impregnation of textiles with resin (2) Curing in 2 steps: RT/24 h, 75°C in a stove [42] Flax fiber epoxy composites…”
Section: Procedures Referencementioning
confidence: 99%
“…Tensile strength of carbon-/flax-epoxy composites and nonhybrid carbon-and flax-epoxy composites[9,12,13,17,19,21,23,25,26,[40][41][42][43][44][45][46][47][48][49][50][51] 9. International Journal of Polymer Science…”
mentioning
confidence: 99%
“…Braga et al [11] demonstrated the mechanical properties and the microstructure of hybrid jute-glass /epoxy composites and found that the physical and mechanical properties of this hybrid were significantly improved. Tensile and shear properties of epoxy composite reinforced by two different types of fibers, unidirectional (glass and carbon) and woven fibers (glass, aramid and carbon), were investigated [12]. Tensile properties of aramid fiber of the woven type are higher than that the glass and carbon fibers.…”
Section: Introductionmentioning
confidence: 99%